Simple preparation of novel photochromic polyvinyl alcohol/carboxymethyl cellulose security barcode incorporated with lanthanide‐doped aluminate for anticounterfeiting applications - Alfi, Alia Abdulaziz; Al‐Qahtani, Salhah D.; Alatawi, Nada M.; Attar, Roba M. S.; Abu Al‐Ola, Khulood; Habeebullah, Turki M.; El‐Metwaly, Nashwa M. (Luminescence (Chichester, England), 2022)
Forgery and low‐quality products pose a danger to society. Therefore, there are increasing demands for the production of easy‐to‐recognize and difficult‐to‐copy anticounterfeiting materials. Products with smart photochromic and fluorescence properties can change colour and emission spectra responding to a light source. In this context, we devised a straightforward preparation of a luminescent polyvinyl alcohol/carboxymethyl cellulose (PVA/CMC) nanocomposite to function as a transparent labelling film. The lanthanide‐doped aluminate (LdA) was prepared in the nanoparticle form to indicate diameters of 35–115 nm. Different ratios of the LdA were physically dispersed in the PVA/CMC nanocomposite label film to provide photochromic, ultraviolet protection, antimicrobial activity, and hydrophobic properties. Fluorescence peaks were detected at 365 and 519 nm to indicate a colour change to green. As a result of increasing the phosphor ratio, improved superhydrophobic activity was achieved as the contact angle was increased from 126.1° to 146.0° without affecting the film's original physical and mechanical properties. Both ultraviolet (UV) light protection and antibacterial activity were also investigated. The films showed a quick and reversible photochromic response without fatigue. The current strategy reported the development of a photochromic smart label that is transparent, cost effective, and flexible. As a result, numerous anticounterfeiting products can benefit from the current label for a better market. LdA‐loaded PVA/CMC films demonstrated antibacterial activity between poor, good, very good, and outstanding as the percentage of LdA in the film matrix increased. The current film can be applied as a transparent photochromic security barcode for anticounterfeiting applications and smart packaging. A transparent photochromic ecofriendly composite anticounterfeiting label was developed. Different phosphor ratios were physically dispersed in the nanocomposite label. The fluorescence peak was detected at 519 nm to indicate UV‐induced green emission. Improved superhydrophobic, UV protection, and antibacterial activity were detected. The films showed quick and reversible photochromic response without fatigue.